2017
DOI: 10.1103/physrevmaterials.1.034606
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Bi atoms in InP studied at the atomic scale by cross-sectional scanning tunneling microscopy

Abstract: We show the potential of cross-sectional scanning tunneling microscopy to address structural properties of dilute III-V bismides by investigating Bi:InP. Bismuth atoms down to the second monolayer below the {110} InP surfaces, which give rise to three classes of distinct contrast, are identified with the help of density functional theory calculations. Based on this classification, the pair-correlation function is used to quantify the ordering of Bi atoms on the long range. In a complementary short-ranged study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 45 publications
2
8
1
Order By: Relevance
“…Remarkably, it was also shown that the computed STM images were in excellent agreement with the measured images only when the tip orbital consisted of a dominant d z 2 −r 2 /3 orbital, consistent with the earlier prediction for a transition metal tip [24]. This behaviour was in stark contrast to the observed STM images of impurities in direct band-gap semiconductor materials such as GaAs [13,14] and InP [25], where the images of electrons bounded to subsurface Bismuth (Bi), Nitrogen (N), and Antimony (Sb) impurities at various depths were in good agreement with theory based on only s orbital in the tip state.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Remarkably, it was also shown that the computed STM images were in excellent agreement with the measured images only when the tip orbital consisted of a dominant d z 2 −r 2 /3 orbital, consistent with the earlier prediction for a transition metal tip [24]. This behaviour was in stark contrast to the observed STM images of impurities in direct band-gap semiconductor materials such as GaAs [13,14] and InP [25], where the images of electrons bounded to subsurface Bismuth (Bi), Nitrogen (N), and Antimony (Sb) impurities at various depths were in good agreement with theory based on only s orbital in the tip state.…”
supporting
confidence: 87%
“…Therefore, we conclude that for the GaAs:N system, the precise tip orbital composition does not play an important role, and the s orbital Tersoff-Hamann approximation provides a qualitatively accurate understanding of the measurements. This has indeed been true in several recent studies where the computed s orbital images were quite accurate to understand direct band-gap STM experiments [13,14,25].…”
supporting
confidence: 65%
“…In addition, we have recently demonstrated that the structural modifications of the {110} surfaces by Bi atoms down to the second layer can be detected in topographic X-STM measurements. 20 In filled state X-STM images, which are taken at a high negative sample voltage, the large Bi atoms in even or odd numbered layers lead to a displacement of either one or a rectangle of four atoms out of the surface. Similar observations have been made for small N atoms, which give rise to local depressions in the surface with the same symmetry as for Bi.…”
Section: A Classification Of the Main Boron Related Featuresmentioning
confidence: 99%
“…This is essential for a deeper understanding of the mechanism behind the unusually strong influence of Bi on the band structure of its host, which goes beyond the phenomenological band anticrossing (BAC) model [6]. We have used cross-sectional scanning tunneling microscopy (X-STM), which allows the direct imaging nanostructures and impurities below the growth surface without averaging, to address these questions [7].…”
Section: Introductionmentioning
confidence: 99%